2021
DOI: 10.1111/jch.14347
|View full text |Cite
|
Sign up to set email alerts
|

Associations of plasma uromodulin and genetic variants with blood pressure responses to dietary salt interventions

Abstract: Uromodulin, also named Tamm Horsfall protein, have been associated with renal function and sodium homeostasis regulation. The authors sought to examine the effects of salt intake on plasma and urinary uromodulin levels and the association of its genetic variants with salt sensitivity in Chinese adults. Eighty patients from our natural population cohort were maintained sequentially either on a usual diet for 3 days, a low-salt diet (3.0 g) for 7 days, and a high-salt diet (18.0 g) for an additional 7 days. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Retrospective analysis of the DASH-Sodium trial showed that higher urine UMOD levels were not associated with an increase in BP in response to an increase in salt intake [ 11 ]. Recently, an interventional study in a Chinese cohort showed that high salt intake reduced significantly both plasma and urinary UMOD levels [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective analysis of the DASH-Sodium trial showed that higher urine UMOD levels were not associated with an increase in BP in response to an increase in salt intake [ 11 ]. Recently, an interventional study in a Chinese cohort showed that high salt intake reduced significantly both plasma and urinary UMOD levels [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…From April to November 2004, we established the cohort of Baoji Salt-Sensitive Study, which recruited 514 adults from 124 families in seven villages in Baoji city, Shaanxi, China. The detailed study design has been published previously ( 20 22 ). To identify the associations of potential genetic variants with longitudinal BP changes and the incidence of hypertension, we followed this cohort in 2009, 2012, and 2018.…”
Section: Methodsmentioning
confidence: 99%
“…From April to November 2004, we established the cohort of Baoji Salt-Sensitive Study, which recruited 514 adults from 124 families in seven villages in Baoji city, Shaanxi, China. The detailed study design has been published previously (20)(21)(22).…”
Section: Section 1: a Longitudinal Cohort Study To Examine The Associ...mentioning
confidence: 99%
“…This has been reviewed by Padmanabhan et al 46 . Single nucleotide polymorphism variants in the UMOD promoter area have been linked to risk of HTN, 47,48 but such association may be dependent on other factors, including ethnicity (single nucleotide polymorphism variants association with HTN may be different in patients of African descent compared with European or Chinese 49 ). Uromodulin regulation of salt handling, NKCC2 and NCC activity could be the link to HTN.…”
Section: Overview Of Functions and Sites Of Action Of Uromodulinmentioning
confidence: 99%